Information and Communication Technology in Sudan: An Economic Analysis of Impact and Use in Universities - Mohamed Nour, Samia (Springer, 2015)
This book discusses the use, economic importance and impact of Information and Communication Technologies (ICT) in public and private Sudanese universities. The author provides an in-depth analysis of the economic impact of ICT from the demand perspective as well as from the public-private perspective. This book also examines the status, pattern, structure, trend and determinants of the demand for ICT in public and private Sudanese universities. It investigates the economic impacts of the uses of ICT, the potential opportunities and challenges that ICT is expected to create for public and private Sudanese universities, and explains the role of ICT in facilitating the production, creation and transfer of knowledge in Sudanese universities.